In silico analysis to identify novel ceRNA regulatory axes associated with gallbladder cancer - Saklani, Neeraj; Chauhan, Varnit; Akhtar, Javed; Upadhyay, Santosh Kumar; Sirdeshmukh, Ravi; Gautam, Poonam (Frontiers in Genetics, 2023)
Competitive endogenous RNA (ceRNA) networks are reported to play a crucial role in regulating cancer-associated genes. Identification of novel ceRNA networks in gallbladder cancer (GBC) may improve the understanding of its pathogenesis and might yield useful leads on potential therapeutic targets for GBC. For this, a literature survey was done to identify differentially expressed lncRNAs (DELs), miRNAs (DEMs), mRNAs (DEGs) and proteins (DEPs) in GBC. Ingenuity pathway analysis (IPA) using DEMs, DEGs and DEPs in GBC identified 242 experimentally observed miRNA-mRNA interactions with 183 miRNA targets, of these 9 (CDX2, MTDH, TAGLN, TOP2A, TSPAN8, EZH2, TAGLN2, LMNB1, PTMA) were reported at both mRNA and protein levels. Pathway analysis of 183 targets revealed p53 signaling among the top pathway. Protein-protein interaction (PPI) analysis of 183 targets using the STRING database and cytoHubba plug-in of Cytoscape software revealed 5 hub molecules, of which 3 of them (TP53, CCND1 and CTNNB1) were associated with the p53 signaling pathway. Further, using Diana tools and Cytoscape software, we constructed novel lncRNA-miRNA-mRNA networks regulating the expression of TP53, CCND1, CTNNB1, CDX2, MTDH, TOP2A, TSPAN8, EZH2, TAGLN2, LMNB1, PTMA. These regulatory networks may be experimentally validated in GBC and explored for therapeutic applications.